Windows vista step by step - Preppernau, Joan (Step by step (Redmond, Wash.), 2008)
Offers a tutorial showcasing the functions and features of Window's newest operating system, while reviewing such Windows basics as installation and customization, document and file management, networking, e-mail, and multimedia features.